Kekayaan Jenis dan Distribusi Anggrek Terestrial di Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Sawala Mandapa, Majalengka: Species Richness and Distribution of Terrestrial Orchids in the Forest Area with Special Purpose (KHDTK) Sawala Mandapa, Majalengka - Inama, Inama; Santoso, Nugroho Ponco; Raihandhany, Reza; Kurniawan, Firman Heru (Jurnal Sumberdaya Hayati, 2022)
Orchid is a plant species with a very high level of diversity, consisting of 28,000 species including 763 genera. As one of the mega-biodiversity countries, Indonesia has at least 5000 types of orchids scattered in various places. This study aims to inventory the types of Terrestrial Orchids found in KHDTK Sawala-Mandapa, Majalengka Regency, West Java Province. This qualitative research uses the roaming method with the scope of the Sawala-Mandapa area and by recording the type and coordinates of each Terrestrial Orchid encountered. The primary data taken was recorded using a note sheet to record the type and GPS to record the coordinates of the point. The results obtained are that there are at least four types of Terrestrial Orchids found, including; Geodorum densiflorum (Lam.) Schltr; Nervilia concolor (Blume) Schltr; Nervila campestris (J.J. SM) Schltr; and Perystilus djampangensis J. J. Sm. At the species level, soil orchids in both areas tend to have a clustered pattern with the size of each group at each point being 2-126 individuals.